Piarists in Lithuania. An Endeavour to Capture the Essence - Ślusarska, Magdalena (Senoji Lietuvos literatūra, 2025)
As an independent administrative unit, the Piarist Province of Lithuania operated from 1736. Despite the formal division into separate provinces, the Piarists of Lithuania and Poland maintained good mutual relations. In the Grand Duchy of Lithuania, the Order of the Pious Schools was financially and materially supported by the families of the nobility, the gentry, townspeople, and the secular clergy. Educational and religious endowments and individual bequests enhanced the prestige of each patron, donor, and their families, while the Piarists ensured the proper use of the funds entrusted to them and increased the endowment’s assets. This consideration ensured that the colleges were equipped with libraries and teaching materials. In Lithuania, the Piarists used their own set of regulations (Methodus docendi, 1762), which governed the organisation of schools and the curriculum. They also followed the general principles of the Calasanzian Constitutions, which guaranteed autonomy to each province in choosing its educational model. Piarist schools in Lithuania put into practice a vision of Christian education, which they enriched with civic ideals. At the same time, they aimed at ensuring that education was modern, so considerable attention was paid to the natural and experimental sciences and practical skills. The superiors made sure that the young members of the order were properly prepared for their future educational and teaching responsibilities: the Piarists studied at their own colleges (professoria) and also pursued studies abroad. Educational institutions were staffed by qualified teachers. Some of the monks were not only distinguished teachers but also renowned scholars, writers, and translators who left behind a scientific and literary legacy that often went beyond the needs of the school as such. The texts they published reflected the ideals of the intellectual movement of the Age of Enlightenment. In addition, the Piarists served as preachers at Vilnius Cathedral and at the Tribunal.